2013
DOI: 10.1002/nau.22367
|View full text |Cite
|
Sign up to set email alerts
|

Dual involvements of cyclooxygenase and nitric oxide synthase expressions in ketamine‐induced ulcerative cystitis in rat bladder

Abstract: Aims:The aims of the present study were to investigate voiding patterns, tissue constituents and the expressions of cyclooxygenase-2 (COX-2) and nitric oxide synthase (NOS) involved in ketamine-induced ulcerative cystitis in rat urinary bladder. Methods: Thirty Sprague-Dawley rats were distributed into three groups which received saline or ketamine (25 mg/kg/day) for a period of 14 and 28 days. In each group, cystometry was performed weekly and the concentration of ketamine and its metabolites (norketamine) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 24 publications
9
86
2
Order By: Relevance
“…As mentioned by some authors, 7,13,17,18 there could be immunologic and vascular factors involved in KIC that we could not demonstrate with our Impact of ketamine on urothelium model. Nonetheless, this limitation is also an advantage.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…As mentioned by some authors, 7,13,17,18 there could be immunologic and vascular factors involved in KIC that we could not demonstrate with our Impact of ketamine on urothelium model. Nonetheless, this limitation is also an advantage.…”
Section: Discussioncontrasting
confidence: 64%
“…Recent studies on animal models and histologic samples of KIC patients showed important inflammatory processes and macrophage infiltration. 13,15,18 It is clear that the direct effect of ketamine is not the only mechanism involved in KIC. However, in the absence of these other phenomenon, we were able to demonstrate that the sole presence of ketamine was enough to induce apoptosis in human urothelial cells in monolayer and on 3D tissue-engineered VE.…”
Section: Discussionmentioning
confidence: 99%
“…injection 15 ), and iii) a ketamine þ Cox-2 inhibitor group [ketamine combined with COX-2 inhibitor (parecoxib sodium; Dynastat [Pfizer, New York, New York]) 10 mg/kg per day by i.p. injection 23 ]; each group was treated for 28 days.…”
Section: Animals and Ketamine Administrationmentioning
confidence: 99%
“…As previously described, 15,24 the rats were placed in individual KDS-TL380 metabolic cages and the MLT0380 transducer (AD Instruments, Colorado Springs, CO). Micturition Q12 frequency and the volume of urine output were recorded for 3 days, and a mean value was determined.…”
Section: Physical Indicators Of Bladder Functionmentioning
confidence: 99%
See 1 more Smart Citation